2023
DOI: 10.1007/s11883-023-01109-y
|View full text |Cite
|
Sign up to set email alerts
|

Eggs and Cardiovascular Disease Risk: An Update of Recent Evidence

Abstract: Purpose of Review This review summarizes recent evidence published since a previous review in 2018 on the association between egg consumption and risk of cardiovascular disease (CVD) mortality, CVD incidence, and CVD risk factors. Recent Findings No recent randomized controlled trials were identified. Evidence from observational studies is mixed, with studies reporting either an increased risk or no association of highest egg consumption with CVD mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…If one is concerned about cholesterol in those choline rich foods, they can consume alternative food items that are high in choline but low in cholesterol, such as soybeans, fish, potatoes, mushrooms, and cruciferous vegetables [ 29 ]. However, there is no clear association between egg consumption and cardiovascular disease mortality [ 46 ], and some studies found that egg consumption may even improve lipoprotein profiles [ 47 ] or suppress ischemic heart diseases [ 48 ]. According to a recent study, consuming 7–14 eggs/week as part of a balanced diet can be beneficial for most people [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…If one is concerned about cholesterol in those choline rich foods, they can consume alternative food items that are high in choline but low in cholesterol, such as soybeans, fish, potatoes, mushrooms, and cruciferous vegetables [ 29 ]. However, there is no clear association between egg consumption and cardiovascular disease mortality [ 46 ], and some studies found that egg consumption may even improve lipoprotein profiles [ 47 ] or suppress ischemic heart diseases [ 48 ]. According to a recent study, consuming 7–14 eggs/week as part of a balanced diet can be beneficial for most people [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study by Qin et al involving 0.5 million Chinese individuals revealed a strong link between cardiovascular disease and egg yolk consumption [55]. Carter et al highlighted population-specific factors as the reason for the disparity between these findings [56].…”
Section: Controversies Colluding and Conflicting Studiesmentioning
confidence: 95%